HYDRODYNAMIC REGIME AND WATER EXCHANGE IN NAI LAGOON, NINH THUAN PROVINCE - An, Pham Hai; Quan, Nguyen Van; Tien, Pham Van (Vietnam Journal of Marine Science and Technology, 2016)
This study presents the researching results of the characteristics of hydrodynamic regime and the water exchange in Nai lagoon in Ninh Thuan province and the impact of change in embankment system according to simulation by using numerical models. By application of 3-dimensional MIKE 3 model, the pattern has been established to verify the data of water levels. Calculation is set up in July and in October (representing wet and dry seasons in the region). The simulation results show that in October tidal amplitude is greater than that in July. The flow rate in the center of the lagoon is small, an average of about 2 cm/s, the largest not exceeded 4 cm/s. Regime of water exchange between Nai lagoon and the sea is differences in the rainy and dry seasons. The effect of changes in size of embankment system on hydrodynamic regimes and water exchange of Nai lagoon is also analyzed, evaluated.